2011
DOI: 10.4149/neo_2011_05_396
|View full text |Cite
|
Sign up to set email alerts
|

The effects and mechanisms of blockage of STAT3 signaling pathway on IL-6 inducing EMT in human pancreatic cancer cells in vitro

Abstract: Aberrant Signal transducers and activators of transcription-3 (STAT3) signaling pathway is a major cause of tumor invasion and metastasis; the underlying mechanisms, however, are not well understood. Epithelial-mesenchymal transition (EMT) is an early event that occurs during invasion of cancers of an epithelial origin. It remains elusive whether STAT3signaling pathway is involved in EMT. The objective of this study was to evaluate the effect of blockage of STAT3 signaling pathway on IL-6 inducing EMT in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 44 publications
3
62
1
Order By: Relevance
“…It is reported that both Akt/mTOR and STAT-3 pathways were upstream pathways controlling both EMT and expression of MMP-2 and MMP-9 [15][16][17][18]. Therefore, we wanted to determine whether PI3K/Akt and STAT-3 pathways were activated upon low-concentration capsaicin treatment.…”
Section: Low-concentration Capsaicin Promotes Migration and Invasion mentioning
confidence: 99%
“…It is reported that both Akt/mTOR and STAT-3 pathways were upstream pathways controlling both EMT and expression of MMP-2 and MMP-9 [15][16][17][18]. Therefore, we wanted to determine whether PI3K/Akt and STAT-3 pathways were activated upon low-concentration capsaicin treatment.…”
Section: Low-concentration Capsaicin Promotes Migration and Invasion mentioning
confidence: 99%
“…However, a significant percentage of gastric cancer patients fail to achieve complete remission, leading to the relapse or poor prognosis [2]. Metastasis has been regarded as an important mechanism underlying tumor relapse after successful surgical resections [3][4][5]. Metastasis is the advanced stage of solid tumor progression and is a multistep process that involves invasion, intravasation, extravasation to distant organs and final growth of the secondary tumor.…”
mentioning
confidence: 99%
“…The serum levels of IL-6 are usually found to be elevated in NPC patients (46). The role that IL-6 plays in the regulation of the growth and invasion of cancer cells has been well demonstrated in various cancer cells such as human melanoma (194), human ductal breast carcinoma (253), renal cell carcinoma (289), ovarian carcinoma cells (243), human oral squamous carcinoma cells (270), head and neck cancer cells (281), human chondrosarcoma cells (286), and human pancreatic cancer cells (112). Ectopic expression of LMP1 in epithelial cells has been shown to result in increased MMP-9 expression (334).…”
Section: The Molecular Mechanisms Of Ebv Infection and The Effects Onmentioning
confidence: 99%